The nucleotide sequences of 5S ribosomal RNAs from four Bryophyta-species. - Katoh, K (1983)
The nucleotide sequences of cytoplasmic 5S rRNA from four bryophytes, Marchantia polymorpha, Lophocolea heterophylla, Plagiomnium trichomanes and Anthoceros punctatus have been determined. These RNAs are 119 nucleotides long except for the Anthoceros RNA that has 118 nucleotides. Their sequences are highly similar to each other (91-99% identity) and are more related to those from seed plants (78-83% identity) than to those from green algae (61-73% identity).